Implementation of Integrative Values of Islamic Education in the Curriculum, Learning Strategies, and Character Building of Students - Wahyu Sihab; Sri Haningsih (Penerbit Hellow Pustaka, 2026)
The integration of Islamic educational values into the national education system is a strategic effort to realize holistic and character-based education. This study aims to analyze the implementation of integrative Islamic educational values within the curriculum, learning strategies, and character formation of students in alignment with the demands of contemporary education. This research employs a descriptive qualitative method through document analysis and literature review of policies and implementation models of Islamic education. The findings reveal that the integration of Islamic values has been carried out through character-based curriculum development, contextual learning, and the inclusion of spiritual values in academic activities. However, its implementation still faces challenges in curriculum consistency, teacher competence, and coordination between educational and religious institutions. Continuous strategies are needed through curriculum innovation, teacher capacity strengthening, and the cultivation of Islamic values within the school environment so that Islamic education not only remains normative but also forms students’ personalities comprehensively.